KAJIAN NILAI ESTETIS TARI JEPIN TALI BINTANG DI DESA KALIMAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Putri, Suci Adelia; Ismunandar, Ismunandar; Tindarika, Regaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Jepin Tali Bintang Dance is a dance that is based on elements of Malay movements. The beauty of this dance needs to be known because there are several objective and subjective assessments. This study aims to describe the aesthetic value contained in the Jepin Tali Bintang Dance through writing and pictures. The method used in this study is a descriptive method with a form of qualitative research and a choreographic aesthetic research approach, as well as semiotic. Data collection techniques using observation techniques, interview techniques, and documentation studies. The technique for testing the validity of the data in this study is the extension of observations and triangulation of sources. Based on the data analysis, it can be concluded that the aesthetic value of the Jepin Tali Bintang Dance can be seen through the harmony of movements, make-up, clothing, and properties used. The tempo of the movements, which tend to be medium and fast, combined with the varied volume of motion and the same energy used, make this dance look dynamic. The harmony of the colors of the clothes and make-up used make this dance look balanced and fulfill the character of a dancer on stage. The beauty of the property is depicted with shapes, colors, and messages that teach kindness to Muslims.